Strategi Kepala Desa Dalam Mengembangkan Destinasi Wisata Untuk Meningkatkan Kesejahteraan Masyarakat Di Desa Gelangsar, Gunung Sari, Lombok Barat - Nisa', Hannatun; Hazim Mukhtarom; Anggun Febriyanti; Fidiatun; Anggun Putri (Journal of Social and Education, 2025)
This research is entitled The Strategy of the Head of Gelangsar Village in Improving Community Welfare Through the Development of Tourist Destinations with the research object of Gelangsar Village, village heads, and the development of tourist destinations. The purpose of this study is to analyze the strategies carried out by the head of Gelangsar village in improving the welfare of the community by utilizing tourist destinations, especially the development of Bukit Tiga Rasa tourism. This study uses a qualitative descriptive method with data collection through observation, interviews, and documentation. The data analysis techniques used include data reduction, data presentation, verification, and conclusion drawn. The results of the study show that the head of Gelangsar village has made various efforts to improve the welfare of the community, one of which is by developing the tourism sector, including the development of Bukit Tiga Rasa tourism which is expected to improve the economy of the local community.